Study of the concentration effect and structure of multilayer spherical carbon nanoclusters on the carrying capacity of alternative fuels - Ie.V. Polunkin; S.M. Pleskun (Проблеми трибології)
The paper presents the results of tribological studies of the influence of nanoscale additives on the properties of ethanol and biodiesel fuels. The non-monotonic extreme nature of the dependence of the carrying capacity of liquid fuels on the content of nanoscale particles is revealed; this indicator changes most maximally in the region of ultra-low concentrations of nanoparticles (several ppm). The possibility of improving the synthesis and modification of carbon spheroidal nanoclusters by conducting high-frequency high-voltage synthesis in various organic solvents has been shown, which allowed to increase significantly the set of starting materials for the synthesis with the inclusion of various elements in the structure of CNSs. In order to increase the yield of carbon nanospheres during synthesis in the liquid phase, a reactor with a given angle of the interelectrode space was made for the first time for use in the synthesis process of "Jacob's ladder". For the first time, the hypothesis proposal has been made that individual carbon nanoparticles, obtained by high-voltage high-frequency plasma-chemical synthesis, which appear as spheroidal objects in electron microscopic images, are actually twisted coils of linear chain molecules of the polyyne type – carbynes.